Bulgarian Urban Transportation State of Art and Prospects - Breshkov, Ivan (Research Papers, 2005)
Urban transportation is fair condition in Bulgaria. There are some negative tendencies in time of socio-economic changes: decline of passengers, decrease of number of urban lines and transportation vehicles for urban transportation.More of urban transportation companies are private or owned by the municipalities. The analyses of exploitation and economic indexes indicate that the level of them is in worse condition. The main place of analyses is given to find factors which are fluent on the state of art and future development of urban transportation in Bulgaria.A detailed prognosis of future urban transportation development on the EU ecological requirement is made. The main directions for future development are: to save and develop clean urban transportation under introducing the ecological standards and norms, fuel economy and changes of type of fuel for urban vehicles.The author has a rich experience in urban transportation studies, projects, evaluations and other papers in Bulgaria, EU countries and Africa.